Book Reviews. (1st June 2019) - Zehelein, Eva-Sabine; Havlin, Tetiana
Random Families: Genetic Strangers, Sperm Donor Siblings, and the Creation of New Kin, Rosanna Hertz and Margaret K. Nelson (2019) 1st ed., New York: Oxford University Press, 296 pp., ISBN 978-0-19088-827-5, h/bk, $27.95; ISBN 978-0-19088-829-9, e/bk, $17.00Connecting Families? Information & Communication Technologies, Generations, and the Life Course, Barbara Barbosa Neves and Cláudia Casimiro (eds) (2018) Bristol: Policy Press, 324 pp., ISBN 978-1-44733-994-6, h/bk, £60